Usability characteristic & satisfaction of UiTM Kedah website / Mohd Firdaus Mohd Helmi ...[et al.] - Mohd Helmi, Mohd Firdaus; Abdul Rahman, Abd Latif; Ahmad, Azree (2013)
Today almost all public and private organizations have embraced the World Wide Web. According to Turban et al. (2004), the exponential growth in the number of websites among the organization is due to the application of the internet as a business channel. For these organizations, the website has become an important channel as an advertising platform, sales and service support and also serves as the platform for exchanging information via the intranet and extranet. Although websites provide benefits as mentioned above, the websites need to be usable in order to achieve a high user satisfaction. The problem faced by users has long attracted previous researchers for example Pollock and Hockley (1997) found that very few users were impressed with the quality of information the Internet contained. Against this background many studies have been conducted to investigate the usability of websites. In particular, studies on the usability of universities’ websites have received much attention among researchers. Nonetheless, studies on the same topic in the context of Malaysian universities are still very scarce. To this effect, this study attempts to address this gap by investigating the usability of the UiTM Kedah website. The conduct of the study is driven by the following objectives which are to measure the level of satisfaction and level of usability assessment of the UiTM Kedah website as well as to identify any relationship between usability and satisfaction.